FAMILIAL VALVULAR PULMONIC STENOSIS INVOLVING THREE SIBLINGS - El-Said, Galal M. (Cardiovasc Dis, 1979)
This report describes the cases of three mentally and physically well-developed siblings, 12, 10, and 8 years of age, with varying degrees of isolated valvular pulmonic stenosis not related to age. The severest lesion occurred in the middle patient and was associated with a right-to-left shunt through a patent foramen ovale. The three children had no other siblings, and there was no history of congenital heart disease among close relatives. These cases support the conclusion that genetic factors play a significant role in the development of certain congenital cardiac disorders. IMAGES: